Fictional First Memories. (October 2018) - Akhtar, Shazia; Justice, Lucy V.; Morrison, Catriona M.; Conway, Martin A.
In a large-scale survey, 6, 313 respondents provided descriptions of their first memory and their age when they encoded that memory, and they completed various memory judgments and ratings. In good agreement with many other studies, where mean age at encoding of earliest memories is usually found to fall somewhere in the first half of the 4th year of life, the mean age at encoding here was 3.15 years. The established view is that the distribution around mean age at encoding is truncated, with very few or no memories dating to the preverbal period, that is, below about 2 years of age. However, we found that 2, 479 first memories (nearly 40% of the entire sample) dated to an age at encoding of 2 years and younger, with 887 (14.1%) dating to 1 year and younger. We discuss how such improbable, fictional first memories could have arisen and contrast them with more probable first memories, those with an age at encoding of 3 years and older.